Psychotherapy as a method of humanitarian cognition in the light of the methodology of L.S. Vygotsky - Kubarev, V.S. (Konsulʹtativnai͡a︡ psikhologii͡a︡ i psikhoterapii͡a, 2016)
In the article the author attempts to make a methodological interpretation of psychotherapy as a method of humanitarian cognition, which has its special objectives, principles and conceptual constructions, different from the ones of the natural science. One of the features of humanitarian cognition is that it is directed on the subject who comprehends the various aspects of his personal being, but not on the object. Relying on methodologies developed by L.S. Vygotsky, the author formulates the main question of the article: what the method of psychology should be in order to meet two conditions. On the one hand, it should be appropriate for subject (not object) comprehending his personal being. On the other hand, it should allow comprehending the being hidden behind the phenomenon. Productive amplification of consciousness based on the principles of development and sign-symbolic mediation is considered to be a version of such a method. The author pays special attention to the phenomenological aspect of the method and especially to the position of the inner observer. In the course of the analysis, psychotherapy is proved to be a method of productive amplification of consciousness which is a specific tool of cognition in humanitarian science. В статье предпринимается попытка методологического осмысления психотерапии как метода гуманитарного познания, которое имеет свои особые, отличные от естественнонаучного, цели, принципы и понятийные конструкции. В качестве одной из особенностей гуманитарного познания обозначается то, что его предметом выступает не объект, а осознающий различные аспекты своего личностного бытия субъект. С опорой на методологические разработки Л.С. Выготского формулируется основной вопрос статьи: каким должен быть метод психологии, чтобы он, с одной стороны, был адекватен познанию осознающего свое личностное бытие субъекта (а не объекта) и, с другой стороны, позволял познавать бытие, скрытое за явлением? В качестве его варианта рассматривается метод продуктивной амплификации сознания, в основе которого лежат принципы развития и знаково-символической опосредованности. Особое внимание уделяется феноменологическому аспекту метода и связанной с ним позиции внутреннего наблюдателя. В свете проделанного анализа психотерапия обосновывается как метод продуктив- ной амплификации сознания, являющийся специфическим инструментом познания в науке гуманитарного типа.